Triple captured iron by defect abundant NiO for efficient water oxidation. Issue 6 (16th February 2022) - Zhou, Ya-Nan; Wang, Feng-Ge; Zhou, Jian-Cheng; Dong, Bin; Dong, Yi-Wen; Liu, Xin; Liu, Bin; Yu, Jian-Feng; Chai, Yong-Ming
Abstract : Fe-doped NiO host (Fe–NiMoO4 @NiO-30) with a large surface area is designed to achieve the triple capture of Fe via adjustable surface reconstruction and impregnation to optimize the OER activity and durability of bimetallic NiFe hydroxides. Abstract : An Fe-doped NiO host in a well-defined nanorod assembly (Fe–NiMoO4 @NiO-30) with a large surface area is designed to achieve the triple capture of Fe via adjustable surface reconstruction and impregnation to optimize the OER activity and durability of bimetallic NiFe hydroxides. The defective and robust NiO layer can not only ensure the first capture of Fe atoms through fast impregnation, but also prevent structural collapse and maintain large Fe adsorption layers. In addition, Fe is found to promote the reconstruction process, leading to more defects to facilitate the second capture. Moreover, the reconfiguration can be controlled by adjusting the ratio of Fe and Ni, obtaining appropriate and uniform dynamically stable Fe sites followed by the third trapping. This triple capture can maintain the dynamic balance of the dissolution and redeposition of active species. Thus, an elevated catalytic performance can be expected with an overpotential of 275 mV at 100 mA cm −2 and favorable durability.